DAMPAK TPST BANTAR GEBANG TERHADAP KONDISI SOSIAL MASYARAKAT DI KELURAHAN SUMUR BATU KECAMATAN BANTAR GEBANG - Arnanda Gusmawan Suseno; purwoko .; Nunik Herawati (Journal of Politic and Government Studies, 2018)
Bantar Gebang TPST as a garbage processing facility in Bekasi which is now owned by DKI Jakarta has positive and negative effect for social change in Bantar Gebang area. So this study aims to analyze what are the social impacts negatively and positively felt by residents living in the TPST area. For that writer analyze by using social change theory of Selo Soemardjan and seen from scavenger point of view and society in TPST area in Sumur Batu Village that feel impact from TPST. The result of this research is not only the negative impact of TPST, but also the positive impact is known by the author when doing this research.This study used descriptive qualitative method. The type of descriptive research is the problem solving procedure studied by describing the subject / object of research in accordance with the facts and about an ongoing process in the field. In obtaining the data, researchers conducted an interview on the Bantar Gebang TPST and the residents who became scavengers and residents who live there. The result of the research has been done not only the positive and negative side of Bantar Gebang TPST, but the writer also found that the takeover done by DKI Jakarta to take over Bantar Gebang TPST. Take over is also changing the economy, environment and social in the Village Sumur Batu Bantar Gebang Subdistrict. There are many good changes when managed by DKI Jakarta such as increased compensation money.The writer's suggestion for DKI Jakarta is to pay more attention to the affected communities of Bantar Gebang TPST because there are still many who have not been recorded yet to get the compensation promised by DKI Jakarta, and assist them in the management to get the right.Keywords: Bantar Gebang TPST, social change, scavenger, impact of TPS